Social Support in Older Adults in Asia: Bibliometric Study and Narrative Review - Antonina Ayuning Budi; Wulan Miranda Panggabean; Annastasia Ediati (Green Publisher, 2025)
Older adults are increasingly vulnerable to psychological and social challenges, including depression, loneliness, anddiminished quality of life. This study aims to examine the research trends on social support among elderly populations in Asia, map the core themes of existing literature, and synthesize empirical findings related to social support and well-being.The study combines two approaches, namely a bibliometric analysis (using VOSviewer) of articles from the SCOPUS database (2015–2025) and also a narrative review of eleven peer-reviewed articles from major academic databases. The bibliometric analysis reveals a fluctuating but increasing interest in this topic over the past decade, with medicine, social sciences, and psychology being the dominant fields. The narrative synthesis identifies key correlates of social support, including age, educational level, marital status, living arrangements, and cultural background. Higher perceived socialsupport is associated with reduced loneliness and depression, and improved mental health and quality of life. Social engagement and strong social networks are found to buffer psychological distress among older adults, especially in cultures where filial responsibilities are emphasized. This review underscores the need for family- and community-based interventions and highlights the importance of culturally responsive eldercare strategies in Asia.